In Situ Cosmogenic 10Be Dating of Laurentide Ice Sheet Retreat from Central New England, USA - Jason S. Drebber; Christopher T. Halsted; Lee B. Corbett; Paul R. Bierman; Marc W. Caffee (Geosciences, 2023)
Constraining the timing and rate of Laurentide Ice Sheet (LIS) retreat through the northeastern United States is important for understanding the co-evolution of complex climatic and glaciologic events that characterized the end of the Pleistocene epoch. However, no in situ cosmogenic 10Be exposure age estimates for LIS retreat exist through large parts of Connecticut or Massachusetts. Due to the large disagreement between radiocarbon and 10Be ages constraining LIS retreat at the maximum southern margin and the paucity of data in central New England, the timing of LIS retreat through this region is uncertain. Here, we date LIS retreat through south-central New England using 14 new in situ cosmogenic 10Be exposure ages measured in samples collected from bedrock and boulders. Our results suggest ice retreated entirely from Connecticut by 18.3 ± 0.3 ka (n = 3). In Massachusetts, exposure ages from similar latitudes suggest ice may have occupied the Hudson River Valley up to 2 kyr longer (15.2 ± 0.3 ka, average, n = 2) than the Connecticut River Valley (17.4 ± 1.0 ka, average, n = 5). We use these new ages to provide insight about LIS retreat timing during the early deglacial period and to explore the mismatch between radiocarbon and cosmogenic deglacial age chronologies in this region.